Prinsip Rendah Hati Dalam Kepemimpinan Yosua Sebagai Role Model Pemimpin Masa Kini - Sahat Martua Sinaga; Ryna Heppy Tambunan (STTI Harvest Semarang, 2021)
AbstractThe leadership capacity develops through a process to become a great leader, who carries out leadership with full responsibility, and completes it with a good reputation. With a qualitative method of applying the principles of biblical hermeneutics, an in-depth analysis of Joshua's leadership journey is carried out as a role model for today's leaders. It is clear one of the determining factors is humility. Joshua is a man of humility. He wants to be guided, equipped and through learning by doing his leadership capacity will develop optimally. Joshua's humility was in line with his spiritual maturity. He is a leader who has faith and is loyal to God, a man of faith and trust in God; a man of God's word; and a man of prayer. It is very important for a leader to be humble as the outcome of the spiritual maturity so that person as a leader is able to achieve goals, free from scandals, and complete it with a good reputation.Keywords: Humility, Leadership, Joshua, Role Model